Recent advances in the treatment of functional dyspepsia and irritable bowel syndrome - Bieniasz, Jan; Bigos, Paula; Dendys, Konrad; Kuźnicki, Wojciech; Matkowski, Igor; Potyrała, Piotr (Journal of Education, Health and Sport, 2023)
Introduction and purpose: While irritable bowel syndrome (IBS) and functional dyspepsia (FD) are common problems in everyday clinical practice, their treatment often remains inefficient. The aim of our work is to present the newest discoveries and research conducted in the topic, while putting special accents on methods available in Poland. We decided to refer to British Society of Gastroenterology guidelines of treatment of IBS and FD as commonly accepted treatment standards in Europe. Description of the state of knowledge: Number of patients suffering from IBS and FD remains high. According to current research, there are some new therapeutical options in IBS: fecal microbiota transplant, spinal catepsin S, olorinab and tenapanor. Methods already being in use in other applications such as vitamin D supplementation, losartan and fecal microbiota transplant are also being investigated. Fecal microbiota transplant seems the most promising one. There are no new treatment options in FD, however there are new research on already used rifaximin and prokinetics, which show their efficacy. Intensive research is being conducted on the use of herbal medicines in treatment of FD. Even though some papers prove the effectiveness of acupuncture we have decided to omit this topic due to its controversial nature. Conclusions: Treatment of IBS and FD remains difficult, there are few advances in that area. Unconventional methods such as herbal medicine and fecal microbiota transplant seem to be gaining in importance.